Adverse events associated with amlodipine: a pharmacovigilance study using the FDA adverse event reporting system - Jiang, Jiazhen; Zhong, Qian; Zhou, Xinyu; Zhou, Lisi; Zheng, Jiyuan; Liu, Bingshuo; Di, Xingwei (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAmlodipine, a widely prescribed clinical medication, is associated with adverse reactions that can impede the proper execution of treatment regimens. The lack of systematic studies on amlodipine's adverse drug reactions (ADRs) necessitates further investigation to facilitate refined population management and optimize therapeutic outcomes.MethodThis study leveraged the FDA Adverse Event Reporting System (FAERS) database, extracting reports submitted exclusively by healthcare professionals where amlodipine was designated as the primary suspect (PS). Four risk signal detection methods were employed: Ratio of Odds Ratio, Proportional Reporting Ratio, Bayesian Confidence Propagation Neural Network, and Empirical Bayes Geometric Mean, to conduct a comprehensive analysis of amlodipine-related ADRs. Furthermore, subgroup analyses stratified by gender and age were performed, with multivariable logistic regression utilized to validate the reliability of the findings.ResultsAcross the general population, male cohort, female cohort, elderly group, and younger demographic, the four signal detection methods collectively identified 513, 348, 403, 246, and 260 potential ADRs associated with amlodipine, respectively. Intersection analysis revealed 27 common ADRs, including gingival hypertrophy, vasoplegia syndrome, and distributive shock. Subsequent multivariable logistic regression confirmed amlodipine's role as an independent risk factor for all 27 ADRs (OR > 1, P < 0.05).ConclusionThis study provides compelling evidence that amlodipine poses risks of peripheral edema, shock, and dyspnea, among others. Additionally, it identified previously unreported ADRs such as abnormal full blood count and personality disorder. These findings underscore the importance of exercising caution when prescribing amlodipine to high-risk individuals with a history of hyperkalemia, cardiac structural abnormalities, or airway obstruction.